2021
DOI: 10.1111/obr.13209
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparities in physical activity, sedentary behavior and sleep patterns among 6‐ to 9‐year‐old children from 24 countries in the WHO European region

Abstract: Physical activity, sedentary behavior, and sleep are important predictors of children's health. This paper aimed to investigate socioeconomic disparities in physical activity, sedentary behavior, and sleep across the WHO European region. This cross-sectional study used data on 124,700 children aged 6 to 9 years from 24 countries participating in the WHO European Childhood Obesity Surveillance Initiative between 2015 and 2017. Socioeconomic status (SES) was measured through parental education, parental employme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 71 publications
2
43
0
Order By: Relevance
“…The public health challenge of insufficient physical activity (PA) among children and adolescents has been well documented ( Music Milanovic et al, 2021 ). Not getting enough physical activity can raise the risk of developing many non-communicable diseases, such as heart disease, diabetes, and cancers ( Lona et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The public health challenge of insufficient physical activity (PA) among children and adolescents has been well documented ( Music Milanovic et al, 2021 ). Not getting enough physical activity can raise the risk of developing many non-communicable diseases, such as heart disease, diabetes, and cancers ( Lona et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that physical activity can improve emotional and cognitive abilities and reduce depression and anxiety symptoms ( Borland et al, 2022 ), also enhance the experience of well-being in children and adolescents ( Lema-Gomez et al, 2021 ). Early childhood is a crucial period during which children have sufficient opportunities to develop healthy habits that could be maintained from adolescence to adulthood ( Music Milanovic et al, 2021 ). Despite the widely known benefits of physical activity, many young people do not meet recommended levels of physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…al. showed that 70.9% of children from families with low parental education spent less than 2 h/week on sports compared with 38.2% of children with high parental education [9]. Other important disparities in child and youth physical activity are connected to gender, ethnicity and physical or mental disability [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing tendency to a sedentary lifestyle and insufficient physical activity, even in childhood, in most high-income countries contributes to raise this issue [ 11 ]. In the last few decades, several studies have already documented that children and adolescents from most high-income countries have become less physically active and more sedentary [ 12 , 13 ]. Screen time behaviors, such as watching TV, playing videogames or using computers for other purposes, such as social media or surfing the internet, have all contributed to the overall increase in sedentary time.…”
Section: Introductionmentioning
confidence: 99%